33
Аноним
Математика
14 января 00:44

Упростите выражение: а) 2√27-√12 б) 0,5√128+3√2+2√32

Ответ или решение1

Щербакова Оля

Упростим выражение, используя свойство корня √(a * b) = √a * √b.

1) 2√27 - √12 = 2√(9 * 3) - √(4 * 3) = 2√9 * √3 - √4 * √3 = 2 * 3 * √3 - 2√3 = 6√3 - 2√3 = 4√3.

√9 = 3;

√4 = 2.

2) 0,5√128 + 3√2 + 2√32 = 0,5√(68 * 2) + 3√2 + 2√(16 * 2) = 0,5√68 * √2 + 3√2 + 2√16 * √2 = 0,5 * 8 * √2 + 3√2 + 2 * 4 * √2 = 4√2 + 3√2 + 8√2 = 15√2.

√64 = 8;

√16 = 4.

0 / 10000
ВходРегистрация

Вход

или

Регистрация